Prefrontal cortex infusion of beta‐hydroxybutyrate, an endogenous NLRP3 inflammasome inhibitor, produces antidepressant‐like effects in a rodent model of depression - Naofumi Kajitani; Masaaki Iwata; Akihiko Miura; Kyohei Tsunetomi; Takehiko Yamanashi; Ryoichi Matsuo; Tsuyoshi Nishiguchi; Saki Fukuda; Mayu Nagata; Midori Shibushita; Takahira Yamauchi; Shenghong Pu; et al. (Wiley, 2020)
Abstract Aims Neuroinflammation is deeply related to the pathophysiology of depression. Beta‐hydroxybutyrate (BHB), which is an endogenous ketone body, exerts anti‐inflammatory effects, and peripheral administration of BHB induces antidepressant effects in an animal model of depression; however, it is unclear whether BHB specifically mediates these actions in the brain. Thus, we administered BHB directly into the brain in a rodent model of depression using a chronic unpredictable stress (CUS) paradigm. Methods BHB was continuously microinjected into the prefrontal cortex (PFC) using osmotic pumps for 21 days. Behavioral testing included the forced swim test (FST) and the open field test (OFT); the levels of pro‐inflammatory cytokines, such as interleukin 1β (IL‐1β) and tumor necrosis factor α (TNF‐α), were quantified in the PFC, and the concentration of corticosterone in blood serum was measured. Results BHB administration into the PFC significantly decreased immobility time in the FST, without significantly altering locomotor activity assessed in the OFT. Also, CUS significantly increased the levels of TNF‐α in the PFC and decreased serum corticosterone levels; these changes were attenuated by BHB administration. These findings suggest that a small amount of BHB administered into the PFC directly produces antidepressant effects, possibly through anti‐inflammatory mechanisms, and can improve hypothalamus‐pituitary‐adrenal axis responses. Conclusion BHB may be a novel therapeutic candidate for the treatment of depression based on the neuro‐inflammatory hypothesis, and the PFC is a region implicated in the antidepressant action of BHB.